PENGLIBATAN ORANG CINA DALAM GERAKAN KOMUNIS DI SARAWAK, 1924-1974 - Ling, Ho Hui (SEJARAH: Journal of the Department of History, 2017)
The beginning of the Communist movement in Sarawak could be traced back to the 1924 when the Kuomintang (KMT) branch was established in Sarawak. In the Sarawak communist movement, almost all involved were Chinese, and they were the largest group sympathetic to the communist cause. They were exposed to communist teachings through Chinese schools, periodicals, labour and plantation unions, and political establishments. The communist movement then turned to armed struggle when the Malaysian plan was announced, and then the Federation of Malaysia was formed on 16 September 1963. However, the spread of communist ideology among the Chinese and their involvement in the movement alarmed the government, as the Chinese were an important group, especially in the development of economy and because they formed the second largest ethnic community in Sarawak. The government acted to limit communism from spreading further in Sarawak, by launching military operations and controlling newspaper publications, Chinese schools, and political organisations and activities. The communist problem in Sarawak finally faded with the success of the government-launched Sri Aman Operation in 1974.